Gender and Country of birth inequalities in occupational diseases compensation rate in Italy: INAIL data base analysis (2010-2013) - Salerno, Silvana (La Medicina del Lavoro, 2018)
Background: In Italy and in Europe occupational diseases (OD) claims are growing among women, and international studies show women’s lower compensation rate. Objectives: Analysis of occupational diseases compensation rate among “Italian” women (country of birth: Italy) and “immigrant” women (country of birth: not Italy) focusing on biomechanical overload of the upper limb, the most common OD in Italy. Methods: INAIL (Italian National Institute for Insurance against Accidents at Work) statistical data (2010-2013) on ascertained OD in Industry-Services (I-S) were analyzed by gender and country of birth with particular attention to biomechanical overload of the upper limb and to occupational diseases not included in the official OD list. Results: A significantly lower compensation rate was found among women (Italy: 39% females vs 43% males; not Italy: 32.5% females vs 36% males). Women’s lower success rate was also found for biomechanical overload of the upper limb (Italy: 73% females vs 76% males; not Italy: 64% females vs 70% males), including carpal tunnel syndrome (Italy: 72% females vs 74% males; not Italy: 62% females vs 64% males) and supraspinatus muscle tendinitis (Italy: 71% females vs 79% males; not Italy: 62.5% females vs 72.5% males). Women’s claims were more frequent for OD not in the official list (Italy: 53% females vs 51% males; not Italy: 54% females vs 53% males) and had a lower rate of recognition and compensation (Italy: 13% females vs 19% males; not Italy 10% females vs 14% males). Since 2010 women compensation rate has shown a reduction after the initial amelioration in 2008 when biomechanical overload of the upper limb was included in the official list of OD. Conclusions: An overall lower compensation rate among “Italian” and “immigrant” women was found for biomechanical overload disorders of the upper limb and for not officially recognized occupational diseases. Good gender-oriented preventive practices should be promoted.